PENDAMPINGAN DESA WISATA DALAM MENINGKATKAN KEPUASAN WISATAWAN PADA ERA NEW NORMAL DI DESA WISATA SANGEH - I Made Bayu Wisnawa; Sulistiyo Adi Joko Saharjo; Anak Agung Ratih Wijayanti; Ni Nyoman Nidya Trianingrum; Ni Wayan Mekarini; I Made Hedy Wartana (Universitas Triatma Mulya, 2021)
The Covid-19 pandemic poses a threat as well as an opportunity for tourist villages. Losing tourists is a threat, while improvement to prepare quality tourism is an opportunity. The problems faced by Sangeh Tourism Village are : i) there were still many people who had not implemented health protocols, ii) the potential for village tourism had not been fully offered in tour packages. The mentoring activity for Sangeh Tourism Village aims to increase tourist satisfaction in the normal era. The method used by giving lectures and discussions. The results of the activity show: i) increased public awareness regarding the application of health protocols, ii) the formation of natural, cultural and artificial tourism packages.